Impactful research driving UMP forward - UMP, PNC (The New Straits Times Press (M) Bhd., 2017)
High impact research and innovation remains Universiti Malaysia Pahang's (UMP) strength as the higher learning institution continues to win accolades both in Malaysia and abroad.